A conserved α‐proteobacterial small RNA contributes to osmoadaptation and symbiotic efficiency of rhizobia on legume roots. (11th May 2017) - Robledo, Marta; Peregrina, Alexandra; Millán, Vicenta; García‐Tomsig, Natalia I.; Torres‐Quesada, Omar; Mateos, Pedro F.; Becker, Anke; Jiménez‐Zurdo, José I.
Summary: Small non‐coding RNAs (sRNAs) are expected to have pivotal roles in the adaptive responses underlying symbiosis of nitrogen‐fixing rhizobia with legumes. Here, we provide primary insights into the function and activity mechanism of the Sinorhizobium meliloti trans ‐sRNA NfeR1 (Nodule Formation Efficiency RNA). Northern blot probing and transcription tracking with fluorescent promoter‐reporter fusions unveiled high nfeR1 expression in response to salt stress and throughout the symbiotic interaction. The strength and differential regulation of nfeR1 transcription are conferred by a motif, which is conserved in nfeR1 promoter regions in α‐proteobacteria. NfeR1 loss‐of‐function compromised osmoadaptation of free‐living bacteria, whilst causing misregulation of salt‐responsive genes related to stress adaptation, osmolytes catabolism and membrane trafficking. Nodulation tests revealed that lack of NfeR1 affected competitiveness, infectivity, nodule development and symbiotic efficiency of S. meliloti on alfalfa roots. Comparative computer predictions and a genetic reporter assay evidenced a redundant role of three identical NfeR1 unpaired anti Shine‐Dalgarno motifs for targeting and downregulation of translation of multiple mRNAs from transporter genes. Our data provide genetic evidence of the hyperosmotic conditions of the endosymbiotic compartments. NfeR1‐mediated gene regulation in response to this cue could contribute to coordinate nutrient uptake with the metabolic reprogramming concomitant to symbiotic transitions.